2020
DOI: 10.3390/ijms21165825
|View full text |Cite
|
Sign up to set email alerts
|

α1-Microglobulin (A1M) Protects Human Proximal Tubule Epithelial Cells from Heme-Induced Damage In Vitro

Abstract: Oxidative stress is associated with many renal disorders, both acute and chronic, and has also been described to contribute to the disease progression. Therefore, oxidative stress is a potential therapeutic target. The human antioxidant α1-microglobulin (A1M) is a plasma and tissue protein with heme-binding, radical-scavenging and reductase activities. A1M can be internalized by cells, localized to the mitochondria and protect mitochondrial function. Due to its small size, A1M is filtered from the blood into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Therefore, we examined whether Hb or its oxidation products heme and FerrylHb induce A1M expression in the resident cells of atherosclerosis in vitro-those are human aortic endothelial cells (HAoECs), human aortic smooth muscle cells (HAoSMCs) and macrophages. Here we showed that heme induces A1M mRNA expression in cell cultures, supporting previous results in human primary renal proximal tubule epithelial cells [53] and keratinocytes [54]. Whereas A1M protein levels remained below the detection limit when cells were exposed to free heme, FerrylHb induced a significant A1M secretion in all cell types.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we examined whether Hb or its oxidation products heme and FerrylHb induce A1M expression in the resident cells of atherosclerosis in vitro-those are human aortic endothelial cells (HAoECs), human aortic smooth muscle cells (HAoSMCs) and macrophages. Here we showed that heme induces A1M mRNA expression in cell cultures, supporting previous results in human primary renal proximal tubule epithelial cells [53] and keratinocytes [54]. Whereas A1M protein levels remained below the detection limit when cells were exposed to free heme, FerrylHb induced a significant A1M secretion in all cell types.…”
Section: Discussionsupporting
confidence: 91%
“…A1M has previously been shown to be taken up intracellularly by several different human cell types in vitro , e.g., liver cells (HepG2), red blood cells, erythroid cells (K562), kidney cells (primary renal proximal tubule epithelial cells) and keratinocytes [ 25 , 53 , [53] , [58] , [59] , [60] ]. The mechanism behind the uptake, however, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly synthesized in the liver and has a plasma concentration of 20–50 mg/L with a half-life of 2–3 min and clearance via the kidneys [ 18 , 19 , 20 , 21 ]. A1M has been shown to protect against oxidative damage in cells, tissues and organs, including kidneys [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Interestingly, an in vitro study showed reduction in cell death and oxidation markers by A1M in α-particle irradiated cells and bystander cells, emphasizing the role of oxidative stress in radiation damage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%